Valuasi Ekonomi Wisata Pantai di Kabupaten Timor Tengah Selatan - Marini I. Tanuab; Agus A. Nalle; Fredrik L. Benu (Populer: Jurnal Penelitian Mahasiswa, 2025)
Oetune Beach and Kolbano Beach are types of natural tourism in South Central Timor Regency that have potential resources in the form of uniqueness and natural beauty. This study aims to identify factors that influence visitor demand using linear regression analysis and determine the economic value of the two attractions based on individual travel cost analysis (Individual Travel Cost Method/ITCM). Sampling was done using non probability sampling method form of accidental sampling technique on 120 respondents. The results showed that the variables of distance, time and income had a significant effect on Oetune Beach visits with a total economic value of Rp. 140,332,307,667/year, while Kolbano Beach showed that distance, time, education and transportation costs had a significant effect with a total economic value of Rp. 128,566,261,440/year. e first letter of the word phrase.